APONTAMENTOS DE RACISMO NA OBRA ONE PIECE, DE EIICHIRO ODA - ARAÚJO, Anderson Sousa de (2025)
This dissertation examines the representation of racism and its structural implications in the manga One Piece, created by Eiichiro Oda. The study is based on the ideas of several authors, such as Giovana Santana Carlos, Janete L. Santos, Sandra Aparecida Lima Silveira Farias, Joseph Campbell, Nelly Novaes Coelho, and others, who discuss the particularities of Japanese narrative and the theory of the Bildungsroman. The analysis also draws on authors who address black identity and structural racism, such as Stuart Hall, Frantz Fanon, Sílvio Almeida, and Homi Bhabha. The research also investigates how the concepts of identity and structural racism manifest themselves in One Piece, considering both written content and images, treating the manga as a multimodal text, where meaning emerges from the interaction between text and illustrations. The analysis focuses on how Oda discusses racism in the context of the fictional world of One Piece, addressing the political-social impact of anti-racist discourses and the representation of the characters and their social positions. In this sense, the general objective was to explore the representation of racism in Eastern literature, specifically in the manga genre, and to demonstrate the relevance of this type of fiction in the dissemination of social causes. The final result validated manga as a viable object of academic research and confirmed the presence of criticism of racism in Eiichiro Oda's work, highlighting the parallels between manga narratives and social reality.